Applied urban ecology : a global framework - Richter, Matthias, 1964-; Weiland, Ulrike (Wiley-Blackwell, 2012)
Applied Urban Ecology: A Global Framework explores ways in which the environmental quality of urban areas can be improved starting with existing environmental conditions and their dynamics. Written by an internationally renowned selection of scientists and practitioners, the book covers a broad range of established and novel approaches to applied urban ecology. ℗¡ Approaches chosen for the book are placed in the context of issues such as climate change, green- and open-space development, flood-risk assessment, threats to urban biodiversity, and increasing environmental pollution (especially in.